Identification of Erosion and Infiltration Measurement in the Bengo-Bengo Educational Forest, Hasanuddin University - Agung Nugrawan Kutana; Nur Isra; Nisrina Putri Hanifah; Irma Wahyuningtyas; Rahma Yanti Tajuddin (Poltanesa, 2025)
- Soil erosion is one of the most common forms of land degradation in tropical and subtropical regions. At the same time, infiltration is the process of water entering the soil, which affects the hydrological cycle and soil productivity. This study was conducted in the Bengo-Bengo Educational Forest, Hasanuddin University, to identify forms of erosion and measure soil infiltration rates based on topographical variations. This area has the characteristics of a tropical rainforest ecosystem with land cover consisting of Arenga pinnata and Flacourtia sp. trees, as well as flat, moderate, and steep topography. The methods used included direct observation to identify erosion types and measurement of infiltration rates using metal pipes on various types of topography. The study's results revealed two main types of erosion: rill erosion and gully erosion. Rill erosion had an average length of 38.12 meters, width of 0.55 meters, and depth of 0.15 meters, while gully erosion exhibited a deeper and more progressive pattern. Infiltration measurements showed that the highest infiltration rate occurred on flat topography (13.2 cm/hour), followed by moderate topography (4.8 cm/hour) and steep topography (3.6 cm/hour). The study highlights the importance of vegetation cover in soil conservation to reduce erosion risk and enhance infiltration capacity. This study provides a scientific basis for designing sustainable soil and water conservation strategies and managing educational forest areas. These findings also serve as an essential reference for environmental education and land-use policy development.